Comparing the transfection efficiency of cationic monomer ratios in vinylimidazole and aminoethyl methacrylate copolymers - Sahel Soghrati; Jaleh Varshosaz; Mahboubeh Rostami; Mina Mirian; Fariborz Sharifianjazi; Ketevan Tavamaishvili (International Journal of Pharmaceutics: X)
Employing polycations as non-viral gene delivery vectors has been extensively studied owing to their safety, efficiency and possibility of modifying them in an intended way compared with viral vectors. However, the main challenge is finding a biocompatible and transfection-efficient polymer. In this study, 2-aminoethyl methacrylate (A) and 1-vinyl imidazole (V) were copolymerized at three different molar ratios by a free radical polymerization method and novel biocompatible polycations with narrow molecular weight distribution were obtained. The resulting copolymers were used for condensation of plasmid DNA (pDNA) at different N/P ratios followed by physicochemical characterizations of resulting polyplexes. At N/P ratio of 2, the nanoplexes were smaller than 120 nm. The optimum formulations were stable in presence of polyanions and capable of protecting the condensed pDNA against nucleases. The polyplexes having V to A molar ratio of 1:1 were the most efficient carrier in transfecting HeLa cells and were introduced as a promising non-viral vector.